Histopathological findings of renal biopsy in systemic lupus erythematosus - Karki, Sanjit; Shrestha, Roshan; Paudyal, Buddhi; Pandey, Bimal; Ranjitkar, Nora; Sharma, Yuba Raj; Kayastha, Gyan Krishna (Journal of Patan Academy of Health Sciences, 2016)
Introductions: Classifying morphological pattern of renal involvement is important in systemic lupus erythematosus (SLE) for definitive treatment and prognosis. This study aims to analyse the histopathological pattern of glomerula in SLE patients. Methods: This was a retrospective chart review of patients diagnosed with SLE who had renal biopsy during October 2013 to September 2015 at Patan Hospital. Results: There were 38 patients of SLE. Antinuclear antibody (ANA) was positive in all 38 (100 %), Anti-dsDNA seen in 18 (47.4%). Active urinary sediment & proteinuria was seen in 25 (65.8%) patients and proteinuria in 13 (34.2%) patients. Histopathological patterns were of glomerular involvement, ISN Class II in 2 (5.3%), Class III in 2 (5.3%), class IV in 20 (52.5%), Class V in 6 (15.8%) and mixed IV-V in 8 (21.1%). Conclusions: The diffuse proliferative lupus nephritis (ISN Class IV) was the most common pattern of lupus nephritis encountered in our study followed by mixed pattern (ISN Class IV & V) and membranous lupus nephritis (ISN class IV). Journal of Patan Academy of Health Sciences. 2016 Dec;3(2):10-14